The experience of space: A sensorial analysis of the Chapelle Notre-Dame-du-Haut by Le Corbusier (1955) and Bruder Klaus Field Chapel by Peter Zumthor (2007) (EAAE Joint Publishings, 2026)
Although Le Corbusier and Peter Zumthor belong to different generations and their work addresses different issues, both establish connections with the world of the arts and share a concern for the space experience. Given today’s dominance of psychological awareness, research on spatial experience is pertinent for contemporary architectural practice.This paper will analyze the Chapelle Notre-Dame-du-Haut by Le Corbusier (1955) and the Bruder Klaus Field Chapel by Peter Zumthor (2007). The aim is to explore the influence of art on the designs of both architects. Le Corbusier will be examined through his connections with the sculptor Joseph Savina, while Peter Zumthor will be explored through his close relationship with the work of Joseph Beuys. The study of the theoretical work of each author and the analysis of the graphic documentation of each chapel will provide a deeper understanding of how Le Corbusier and Zumthor responded to a shared concern: the experience of space and its relationship with art.The methodology used in this research integrates various documents, such as the theoretical works of Le Corbusier and Peter Zumthor and documentation from both chapels. The findings of this research enable an understanding of how Le Corbusier and Peter Zumthor respond to a similar concern, wherein art plays a significant role in the experience of space. This research will further contribute to the unexplored relationship between the two architects regarding their awareness of spatial experience and the emotions evoked in individuals engaged within these spaces.